Status Report on Sample Preparation Protocols Developed at the LMC14 Laboratory, Saclay, France: From Sample Collection to 14C AMS Measurement. Issue 3 (17th May 2017) - Dumoulin, J-P; Comby-Zerbino, C; Delqué-Količ, E; Moreau, C; Caffy, I; Hain, S; Perron, M; Thellier, B; Setti, V; Berthier, B; Beck, L
Abstract: The main objective of this report is to present the dating process routinely applied to different types of samples at the Laboratoire de Mesure du Carbone 14 (LMC14). All the results and protocols refer to our procedures over the last 5 years. A description of the sorting and chemical pretreatments of the samples as well as the extraction and graphitization of CO2 are reported. Our last study concerning the degradation of the blank level according to the storage time of the targets between graphitization and accelerator mass spectrometry (AMS) measurement is also presented. This article also provides information on how to submit a valid laboratory sample. We give details relating to sampling procedures on site as well as contamination issues relative to the 14 C dating methodology.